A Study on Mental Health of Visually Handicapped Women - Mahalakshmi M.; Velusamy M.A. (Journal of Social Work Education and Practice, 2023)
Women who are visually impaired or blind may face specific stressors related to their physical borders in addition to the stressors that those who are not physically limited face. Some factors may limit this population's exploitation of mental health services as well as problems with mobility, accessibility of mental health professionals, and attitudes about visual impairment and blindness from both the client and the therapist. In this article, we discuss a descriptive study conducted among the visually impaired women to understand their mental health and problems faced by them. Findings of the study points out that, visually impaired have poor adjustment and low mental health. They are also facing low family and social acceptance.